Biocompatible non-covalent complexes of chitosan and different polymers: characteristics and application in drug delivery - Ćirić, Ana; Krajišnik, Danina; Čalija, Bojan; Đekić, Ljiljana (Archives of Pharmacy, 2020)
The formulation of biocompatible drug carriers based on cationic biopolymer chitosan and natural or synthetic polymers represents an important research interest. Therefore, this review aims to perceive their potential in drug delivery. The most investigated chitosan-based polymer blends are polyelectrolyte complexes (PECs) obtained by establishing ionic interactions with biocompatible polyanions as alginates, pectin, xanthan gum, carrageenan, carboxymethylcellulose, and collagen. Depending on the preparation conditions, PECs could be prepared in versatile forms including membranes/films, hydrogel beads, nanoparticles, and microparticles, to achieve controlled (e.g., extended, delayed, colon-specific and pH-dependent) drug delivery. PECs can encapsulate hydrophilic and lipophilic drug substances with different molecular weights. Drug encapsulation allows the preservation of their structure, activity, improvement in absorption efficiency, reduction in adverse effects and long-term stability in vitro and in vivo. The biocompatible structures as non-covalent chitosan-based complexes could be formed also by establishing hydrogen bonds, for example with poly(vinyl alcohol). The swelling of these complexes is not pH-dependent and encapsulated drug substances are often released by already known types of diffusion. Moreover, grafted chitosan derivatives (e.g., carboxymethyl chitosan, trimethyl chitosan, acrylated chitosan) are synthesized to improve water solubility at a wide pH range and enhance the encapsulation capacity of promising PEC-based drug carriers.